Metagenomics for Gut Microbes 2018
DOI: 10.5772/intechopen.72456
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Implications of Intestinal Microbiota in Migratory Birds

Abstract: Understanding the transboundary movement of microorganisms is a significant public health issue. It is possible that large amounts of various bacteria existing on the earth's surface are spreading across borders through migratory birds, but their identities and rates of migration have yet to be elucidated. Although modern bacteriology has advanced based on culture technology, many environmental bacteria may be in a "viable but nonculturable" state. To date, various novel culture-independent detection methods h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Since disinfection treatments for bird feces is not performed like that for humans and livestock, there are possibilities that several live bacteria, along with 50 million migratory birds each year, travel the East Asia-Australia region flyway for a long distance. In order to clarify the dynamic of the microbiota, including pathogenic bacteria and antibiotic-resistant bacteria, as well as to verify their significance in public health and environmental microbiology, research has been performed to analyze the intestinal microbial community associated with migratory birds by NGS [16][17][18][19][20][21][22].…”
Section: Migratory Birds and Flywaymentioning
confidence: 99%
See 1 more Smart Citation
“…Since disinfection treatments for bird feces is not performed like that for humans and livestock, there are possibilities that several live bacteria, along with 50 million migratory birds each year, travel the East Asia-Australia region flyway for a long distance. In order to clarify the dynamic of the microbiota, including pathogenic bacteria and antibiotic-resistant bacteria, as well as to verify their significance in public health and environmental microbiology, research has been performed to analyze the intestinal microbial community associated with migratory birds by NGS [16][17][18][19][20][21][22].…”
Section: Migratory Birds and Flywaymentioning
confidence: 99%
“…by a novel culture-independent method [14,15]. We attempted to explore the stability of the intestinal bacterial communities in migratory birds, the difference in the intestinal bacterial communities among birds at the individual and species levels, and the potential of long-distance movement of antibiotic-resistant bacteria associated with migratory birds [16][17][18][19]. Research on the spread of bacterial populations over vast distances has led to the elucidation of the roles of migratory birds regarding human health risks, thereby enabling the prediction of potential outbreaks based on their migratory patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In different studies mycoplasmas have been demonstrated as part of the intestinal flora of juvenile and adult barn swallows [ 10 – 13 ]. On average 5.5% to 9.6% Mycoplasmataceae were detected in feces samples from barn swallows by molecular biological analysis, which shows a high amount of Mycoplasmataceae in the intestinal flora [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%